221k views
1 vote
Which expression is a linear factor of x6 +x-66?

X+1

X+2

X+4

none of the above

User Tomas Ward
by
5.3k points

2 Answers

2 votes

Answer:

none of the above

Explanation:

User Chocula
by
5.1k points
0 votes

Answer:

Option D.

Explanation:

The given expression is


x^6+x-66

It is a polynomial.

(x-c) is a linear factor of polynomial p(x) if p(c)=0.

Substitute x=-1 in the given expression.


(1)^6+(1)-66=-64\\eq 0

It means (x+1) is not a linear factor of given expression.

Substitute x=-2 in the given expression.


(-2)^6+(-2)-66=-4\\eq 0

It means (x+2) is not a linear factor of given expression.

Substitute x=-4 in the given expression.


(-4)^6+(-4)-66=4026\\eq 0

It means (x+4) is not a linear factor of given expression.

None of the given options are a linear factor of given expression.

Therefore, the correct option is D.

User Mohsenmadi
by
4.5k points